The Role and Concept of Divine Love in the Poetry of Three Generations in the Era of Digitalization - Muhammad Luthfi (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to analyze the role and concept of divine love contained in poetry and thinkers from three generations. This is very important, considering the next generation of the world of literature, especially literature about the concept of Divine love, very much in need of references to develop the ability to express and narrate. The poet Ibn Arabi represents the Middle Eastern Sufism tradition, while Hamzah Fansuri and Emha Ainun Nadjib represent the Archipelago Sufism tradition. This research not only provides input on the role of information systems in the literary world but also attempts to compare the existence of Sufism Nusantara and Sufism Middle East. This research uses literature study. The results of the study revealed that these three poets and thinkers have similarities in terms of recognizing the existence of God. However, they have their own style of language and characteristics in describing closeness to God as reflected in their poetry. The poet Ibn Arabi, has a characteristic in the style of writing his work that is to describe the feeling of love for God by saying the name and expressing the mood like someone is in love with idol of the heart. Meanwhile, Hamzah Fansuri's poetry, uses the style of the language "divine love" by only talking about "Mahbub" or "the lover". Emha Ainun Nadjib described her special characteristics by expressing divine love in response to the love of living beings for beings. In the era of digitalization, the concept of divine love plays an important role as a source of reference in the form of digital literature and can be developed into utopian literature that expresses human life that is exacerbated or enhanced by technological development.Keywords: Poetry, Literature, Digital Era, Divine Love, Poet.